Chrysin suppresses cigarette smoke-induced airway inflammation in mice - Shen, Yongchun (Int J Clin Exp Med, 2015)
Cigarette smoke-induced airway inflammation is one of the most important features of chronic airway diseases. Studies suggest that chrysin possesses strong anti-inflammatory properties and this study aimed to investigate the effect of chrysin on cigarette smoke-induced airway inflammation in mice. Mice with exposure to cigarette smoke were intraperitonealy injected with chrysin (10, 20 mg/kg·d). TNF-α, IL-1β and IL-8 levels in bronchoalveolar lavage fluid were determined by ELISA. MPO level in lung homogenates was tested by a MPO kit. The expression of signaling proteins in lung tissue, phosphorylation ERK and p38 was detected using Western Blot. Cigarette smoke exposure increased the release of inflammatory cytokines TNF-α, IL-1β, IL-8 in bronchoalveolar lavage fluid and the expression of MPO in lung tissue. Chrysin pretreatment inhibited cigarette smoke-induced airway inflammation, inflammatory cytokines release, and MPO expression. Cigarette smoke exposure also increased the expression of phosphorylation ERK and p38, meanwhile, chrysin intervention can inhibit such changes. In summary, chrysin inhibits cigarette smoke exposure-induced airway inflammation in mice, which may partly act through inhibition of ERK and p38 phosphorylation.